“A True Word of a True Thing” The Significance of Verbum for Bernard Lonergan’s Accounts of Critical Realism, Ethical Agency, and Analogical Understandings of the Holy Trinity - Nicholson, Elisabeth June (Université Saint-Paul / Saint Paul University, 2022)
In Verbum: Word and Idea in Aquinas, Canadian theologian and philosopher Bernard Lonergan describes the act of understanding as the triple-weave of 1) intelligere, or understanding-in-act; 2) dicere, or rational consciousness that conditions the possibility for the emergence of understanding; and 3) verbum, or “inner word,” consisting in the intelligent grasp of intelligibility as it inheres in being. Lonergan describes this “verbum”—or Augustine’s verbum cordis—as intending the logos, or the intelligibility and goodness of being, and considers particularly the analogical relationship between understanding and love in the human soul and the procession of the three persons of the Holy Trinity. In Insight and Method in Theology Lonergan draws attention to activities of self-reflection and self-correction that advert to one’s own subjectivity as it (i) understands and knows what is real, (ii) discerns and brings about what is good, and (iii) apprehends analogies between the activities in “the enlargement of consciousness” and those activities in their absolute limit, which can be interpreted as an heuristic analogy for the Triune God. The emanatio intelligibilis that Lonergan first presents in Verbum represents a protean version of the formulations that appear in his later works. In paying attention to what happens in ourselves when we wonder about what is “real” and “good,” and in “catching ourselves in the act” of expanding our horizons, we may recognize that in their “limit” these endeavours might be analogically proportioned to characteristics and activities of the Holy Trinity, opening onto ideas of ipsum esse, or fully actualized being, ipsum intelligere, or perfect understanding, and summum bonum, or the highest good. In presenting Aquinas’s account of the heuristic analogies between the procession of understanding and love in the human soul and characteristic activities of Trinitarian processions, Lonergan has established the conditions of possibility for understanding conscious intentionality, in its fullness, as intending participation in the Triune God, writ large, in Lonergan’s words, in the “luminousness of being.”
Keywords: Bernard Lonergan; Verbum; Isomorphism of Knowing and Being; Critical Realism; Intelligibility of Being; Intelligibility and Ethical Agency